Enhancing Job Performance in Outsourced Employees: Do Reward Systems Matter More Than Empowering Leadership? - Tegar Wicaksana; Ruland Willy Jack Sumampouw (SAN Scientific, 2026)
This study investigates the influence of empowering leadership and reward systems on job performance, with job satisfaction as a mediating variable among outsourced employees at PT Bank Mandiri Tbk in the Bekasi region. Using a quantitative approach, data were collected from all outsourced employees through structured questionnaires measured on a five-point Likert scale and analyzed using PLS-SEM. The findings reveal that empowering leadership does not play a significant role in shaping job satisfaction or improving job performance in this context. In contrast, the reward system emerges as a key factor that positively influences both job satisfaction and employee performance. Interestingly, job satisfaction itself does not significantly contribute to job performance and is unable to mediate the relationship between empowering leadership, reward systems, and performance outcomes. These results suggest that in outsourced employment settings, where job roles and authority are often limited, tangible factors such as fair and transparent rewards are more influential than leadership style or psychological conditions. The study highlights the importance of designing effective reward systems to enhance performance and provides practical insights for organizations managing outsourced employees in achieving better productivity outcomes.